Tools for high performance computing 2015 : proceedings of the 9th International Workshop on Parallel Tools for High Performance Computing, September 2015, Dresden, Germany /: proceedings of the 9th International Workshop on Parallel Tools for High Performance Computing, September 2015, Dresden, Germany. (2016) - Unknown
No abstract available